Conflict in Neighboring Countries, a Great Risk for Malaria Elimination in Southwestern Iran: Narrative Review Article. - Maryam Molaee Zadeh; Khandan Shahandeh; Shahla Bigdeli; Hamid Reza Basseri (Tehran University of Medical Sciences, 2014)
The intensity of the conflict such as war is one of the determinants of the flow of migrants and refuges with consequence of introducing infectious disease to other countries. This paper investigates the relationship between malaria incidence and forced immigration due to war from neighboring countries in Dezful district, southwestern Iran. All available data and accessible archived documentary records on malaria cases in the period 1988-2011 in Dezful Health Centers were reviewed. Retrospective analysis of routine surveillance data from the Health authority of Dezful district was conducted to assess the trend of malaria incidence and prevalence in the last two decades. Malaria transmission dynamics was described using surveillance indicators viz, Annual Parasite Incidence (API), Slide Positivity Rate (SPR), Annual Blood Examination Rate (ABER) and based on personal information of patients. Two peaks of malaria incidence occurred during past two decades. The first one arisen by Iran-Iraq war due to residential instability in Dezful while the API reached to 8 per 1000. The second peak happened after to civil war of Afghanistan began which caused large immigrates moved into the study area. During the second peak, API reached 1.7 per 1000 at maximum and the majority of patients were immigrants. This study describes the linkage between incidence and prevalence of malaria and immigration due to civil conflict. Therefore, malaria screening of immigrants and early warning programme are effective to prevent outbreak of disease in a potential risk area such Dezful.